Revisiting Olaf Caroe’s The Pathans: A Critical Discourse Analysis Perspective - Mehmood, Nasir; Shahzad, Khurram; Hussain, Bilal (Pakistan Journal of Humanities and Social Sciences, 2022)
This article critically evaluates Olaf Caroe’s book “The Pathans” by using the framework of critical discourse analysis”. The book consists of a total of four hundred thirty-eight pages. The study explores how the author has wrongly ascribed the authorship of some passages to Khushhal Khan Khattak. Moreover, it also investigates how certain events of Pathan’s history have been misrepresented. The study is significant as it highlights loopholes in one of the most important books of Pathans history. The text which forms the data for the present study is the chunks selected from “The Pathans”. After evaluating the text, it is found that the author of the book, in some places, presents his weak appraisal of the events and expresses statements that do not conform to the ground realities. Lastly, after a careful analysis of the evidence, the study concludes that the author has insufficient knowledge of the historical events; particularly those concerning Khushhal Khan Khattak, which, ultimately resulted in misinterpretation of the historical facts. Hence the study recommends that there is a dire need to rectify some of the historical events from their true historical perspective.